European Union Resolution and The Profitability: The Role of Size, Difference-In-Differences Analysis - Kaban, Adrianus Herianto; Lindrianasari, Lindrianasari; Ariefianto, Moch. Doddy (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
In this study, we examined the impact of the EU Resolution policy on the profitability of palm oil companies in Indonesia and Malaysia (The two biggest palm oil producers). We develop and estimate difference-in-differences regression model using annual data from 61 listed companies from the year 2014 to the year 2022 with a total of 549 observations. We found that the size of companies in the palm oil industry is a key factor in maintaining profitability in the event of EU Resolution implementation. Not only have larger companies managed to avoid losses from EU resolution; but they even can improve their profitability. The result is robust after a set of tests involving alternative proxies and propensity score matching. We offered a plausible explanation related to the role of size and opened future avenues for further investigation.